Effects of Standardized Ileal Digestible Tryptophan to Lysine Ratio on Growth Performance of PIC Line 337 × 1050 Pigs - Rafe Q. Royall; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Jordan T. Gebhardt; Carine M. Vier; Matthew Spindler; Uislei Orlando; Luis Zaragoza; Ning Lu; Wayne Cast; et al. (Kansas Agricultural Experiment Station Research Reports, 2023)
The objective of these experiments was to evaluate the impact of varying SID Trp:Lys ratios on growth performance, removals, and mortality rates of PIC 337 × 1050 finishing pigs. In each experiment, pens of pigs were blocked by BW and randomly assigned to 1 of 5 dietary treatments in a randomized complete block design with 22 to 27 pigs per pen and 6 or 7 replications per treatment. In Exp. 1, 840 pigs (initially 101.2 ± 2.08 lb) were used from 101 to 161 lb. In Exp. 2, 801 pigs (initially 219.8 ± 3.44 lb) were used from 220 to 281 lb. Dietary treatments were corn-soybean meal-based with 30 or 20% DDGS (Exp. 1 and 2, respectively) and contained increasing SID Trp:Lys ratios at 15, 17.5, 19, 21, and 23%. Diets containing low and high Trp:Lys ratios were blended to achieve the target SID Trp:Lys treatment levels in Exp. 1, while diets containing low, medium, and high Trp:Lys ratios were blended to achieve the target SID Trp:Lys treatment levels in Exp. 2. Between experiments, all pens of pigs were placed on a common diet for 27 d and pens were reallotted to dietary treatment at the start of Exp. 2. In Exp. 1, increasing the SID Trp:Lys ratio increased (quadratic,P≤ 0.008) ADG, ADFI, and final BW and improved (quadratic,P= 0.007) F/G. As expected, increasing SID Trp:Lys increased (linear,P<0.001) Trp intake, g/d. In addition, Trp intake per kg of gain and Lys intake/d increased (quadratic,P≤ 0.009), while Lys intake per kg of gain decreased (quadratic,P= 0.008) with increasing SID Trp:Lys ratio. There was no difference between Trp:Lys ratios on the percentage of removals, mortalities, or total removals (P>0.10). For model analysis in 101- to 161-lb pigs, the developed broken-line linear models suggested no further improvement to ADG and F/G beyond 19.0 and 19.3% SID Trp:Lys, respectively. Meanwhile, a similar fitting quadratic polynomial (QP) model suggested minimum F/G was achieved at 21.5% SID Trp:Lys. In Exp. 2, increasing the SID Trp:Lys ratio increased (linear,P≤ 0.001) Trp intake and Trp intake per kg of gain (quadratic,P= 0.050). However, no other observed response criteria were significantly impacted (P≥ 0.10). Models to predict optimal Trp:Lys ratios were not analyzed for 220- to 281-lb pigs due to the lack of observed differences for ADG and F/G. In summary, these results suggest the optimal SID Trp:Lys level for 101- to 161-lb pigs was predicted at or above 19.0 and 19.3% SID Trp:Lys for ADG and F/G, respectively. With the variation in response criteria observed in Exp. 2 (220 to 281 lb), we were unable to statistically define a requirement estimate.
Keywords: amino acid; grow-finish pigs; tryptophan; nutritional requirements